Evaluation of stability of field pea genotypes in response to Mycosphaerella pinodes infection - Boros, Lech (Plant Breeding and Seed Science, 2012)
Interaction of genotypes with environment for quantitative traits among them certain disease resistance makes difficult choice of proper genotypes for breeding proposes and may affects further cultivation effects. The aim of this study was assessment of stability of reaction to Mycosphaerella pinodes infection for the set of pea genotypes in four years field experiments with vary epidemic pressure. The Sheffé-Caliński mixed model and the Caliński-Kaczmarek joint regression model for genotype-environment interaction analysis was applied. Tested pea genotypes were grouped into two categories; responding stable to M. pinodes (reacting proportionally to changed environment) and unstable ones (showing significant interaction with environment). The unstable genotypes reacted irregularly to environments (not able to describe the reaction to M. pinodes by any linear regression function). Pea genotypes PI 142441, PI 142442, PI 404221, PI 413691, cv. Radley and Bohun were characterized by high negative main effects (most resistant) for disease severity and showed stable response to M. pinodes infection. Stability of mycospharealla blight reactions was not associated with the level of resistance in the cultivars tested.